Neogene marine sediments and biota encapsulated between lava flows on Santa Maria Island (Azores, north‐east Atlantic): An interplay between sedimentary, erosional and volcanic processes. Issue 7 (8th July 2020) - Uchman, Alfred; Johnson, Markes E.; Ramalho, Ricardo S.; Quartau, Rui; Berning, Björn; Hipólito, Ana; Melo, Carlos S.; Rebelo, ANA C.; Cordeiro, Ricardo; Ávila, Sérgio P.
Abstract: Sedimentary rocks are rarely preserved on reefless volcanic oceanic islands because their sediments are mostly exported from coastal areas towards the deep sea and such islands typically undergo subsidence. In contrast, the exceptional geological record of the uplifted Santa Maria Island (Azores) provides a unique opportunity to gain insight on such coastal systems. This study focuses on a locality at Ponta do Cedro (eastern Santa Maria Island), which features a series of marine fossiliferous sediments wedged between steep lava deltas. As demonstrated by local structure, these sediments correspond to clinoforms deposited on the steep submarine slope of an active volcanic island, implying transport from shallow waters to greater depths and subsequent colonization by benthic communities. Rapid volcanic progradation eventually sealed the deposits, allowing for their preservation and providing a rare snapshot of the ecology during those intervals, in addition to insights on sedimentary dynamics along submarine island slopes. This study reveals spatial relationships between wedges of sedimentary bodies encapsulated by lavas in the Ponta do Cedro section, and interprets depositional processes preserved in those strata based on sedimentological and palaeontological data. The dynamics of the environment are mostly related to relative sea‐level changes, intense volcanic activity and regional uplift during the Neogene.